2020
DOI: 10.3390/jcm9051368
|View full text |Cite
|
Sign up to set email alerts
|

Association between Anxiety and Vascular Dementia Risk: New Evidence and an Updated Meta-Analysis

Abstract: The association between anxiety and vascular dementia (VaD) is unclear. We aimed to reliably estimate the association between anxiety and VaD risk using meta-analysis to pool new results from a large community-based cohort (Zaragoza Dementia and Depression (ZARADEMP) study) and results from previous studies. ZARADEMP participants (n = 4057) free of dementia were followed up on for up to 12 years. Cases and subcases of anxiety were determined at baseline. A panel of four psychiatrists diagnosed incident cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
(82 reference statements)
2
8
0
Order By: Relevance
“… 63 Additionally, the role of anxiety in the risk of dementia has been identified in some meta‐analyses. 64 , 65 Consistently, this study found that anxiety and depression were both independently associated with a higher risk of MCI in T2DM patients, highlighting the importance of regular screening for anxiety and depression in T2DM patients to maintain cognitive function.…”
Section: Discussionsupporting
confidence: 74%
“… 63 Additionally, the role of anxiety in the risk of dementia has been identified in some meta‐analyses. 64 , 65 Consistently, this study found that anxiety and depression were both independently associated with a higher risk of MCI in T2DM patients, highlighting the importance of regular screening for anxiety and depression in T2DM patients to maintain cognitive function.…”
Section: Discussionsupporting
confidence: 74%
“…However, regarding some psychosocial factors, such as social support, studies have mostly been limited to child or adolescent samples (Albaugh et al, 2017;Dahmen et al, 2018;Keresztes et al, 2020;Luby et al, 2019;Malhi et al, 2019;Malhi et al, 2020) and focused on total hippocampal volume rather than exploring the differential effect within subfields (Albaugh et al, 2017;Banning et al, 2020;Binnewies et al, 2021;Dahmen et al, 2018;Dannlowski et al, 2012;Gerritsen, van Velzen, et al, 2015;Keresztes et al, 2020;Malhi et al, 2019;Malhi et al, 2020). Further, these psychosocial factors, such as low social support (Miyaguni et al, 2021;Penninkilampi et al, 2018), depression (Byers & Yaffe, 2011;Diniz et al, 2013), anxiety (Kuring et al, 2020;Santabárbara et al, 2020), and childhood maltreatment (Radford et al, 2017), have been associated with an increased risk for incident dementia, which could possibly be mediated by hippocampal volumes (Gruenewald et al, 2020;Linnemann & Lang, 2020;Mah et al, 2016). Therefore, by understanding the role psychosocial factors have on regions of the hippocampus in an adult population, we can better understand how these factors may contribute to the development of neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic outbreak has had substantial mental health impact on healthcare workers (HCWs), largely due to increases in healthcare capacity requirements driving job redeployments and extended working hours in combination with very high risk of contagion and death. Estimates from cross-sectional studies conducted during the initial pandemic outbreak suggest that between 25 and 50% of HCWs may have experienced clinically significant symptoms of anxiety or depression (1)(2)(3)(4)(5)(6)(7) and posttraumatic stress (1,3,7).…”
mentioning
confidence: 99%